INFLUENCE OF STRENGHT OF NERVOUS PROCESSES ON THE DIRECTION OF MANAGEMENT ACTIVITY OF A PERSON - Stepanyan , L. S.; Sumbulyan , G. S. (Modern Psychology, 2019)
This article examines the role of strength of neural processes as the innate and core factors, in the direction and strategy of managerial activity. As a result of the study, the relationship between the strength of the manager's nervous processes and the managerial orientation was revealed. It has been shown that managers with a weak nervous system tend to favor work, and at the same time, their job satisfaction is conditioned by their level of aspiration and achievement. At the same time, it has been found that managers with strong nerve types have a predominant attitude towards people, and job satisfaction is largely due to human interactions.
Keywords: Leadership, management, nervous process strength, management style, job satisfaction.